Potential of Brazilian eugenia myrtaceae - As ornamental and as a fruit crop - Donadio, L. C. [UNESP]; Moro, F. V. [UNESP] (My University, 2004)
Brazilian Myrtaceae comprises several genera of trees and shrubs used for ornamental and fruit production. In addition to the well known Guava, Pitanga and Jaboticaba, other species could be used for fruitculture, due the value and quality of their fruits and adaptation to some climate conditions mainly the subtropical one. Nine species of Eugenia were evaluated at Jaboticabal, located at 48° W and 21° S in São Paulo state in a germplasm bank. The average rain by year is 1431 mm and the temperature 22,2° C at an altitude of 575 m. The species are Eugenia klozschiana Berg. (Pero-do-campo), E. stipitata Mc Vaugh (Araça-boi), E. tomentosa Camb. (Cabeludinha), E. dysentherica DC. (Cagaita), E. brasiliensis Berg. (Grumixama), E.pitanga (Pitanga-anã), E. luchsnathiana Berg. (Pitomba), E. uvalha Camb. (Uvaia) and E. involucrata DC. (Cereja-do-rio-grande). The evaluations comprised tree development, fruit quality and leaf and flower morphological studies. The main results are: the trees of Pera-do-campo and Pitanga-anã are small shrubs of 1 to 2 m height, Araça-boi and Cabeludinha are small trees, 3 to 5 m high, and the other species are tall trees, with 5 to 10 m height. The species adapted well to the subtropical conditions, except for Araça-boi, which is native to the Amazonian region and exhibited a severe fungus disease infection. In relation to fruit quality, all the species had edible fruit, some were sweet and juicy, Cabeludinha, Grumixama, Pitomba, Cereja-do-rio grande and Pitanga-anã, while others had high acidity (Araça-boi, Pera-do-campo, Cagaita and Uvaia and were more suitable for processing. Simple, single leaves were characteristic of all species, but with different sizes and shapes., With the addition of color, smell and other characteristics, leaf size and shape were useful for comparative classification. Flower components and structure are described also.